Mineral and sugar concentrations taken during matches and their effect on some physical and functional abilities of football players - Mahdi , Hamed (Journal of Physical Education, 2025)
Many athletes believe that it enhances the level of performance during training and competition, in addition to compensating for fluids during exercise when the levels of temperature and humidity in the atmosphere rise during the athlete’s intensive training, as it increases the requirements for fluid compensation to avoid the risk of potential thermal disorders. If training continues for more than an hour causing fatigue, athletes are advised to drink carbohydrate drinks that quickly convert to glucose in the blood, while sodium should be included in the fluids consumed during exercise or matches that last more than (1-2 hours). The effect of drinking a drink containing 12% carbohydrates and electrolytes before each half of a simulated football match facilitates the maintenance of passing performance and improves the ability of high-intensity running in football academy players. This study aims to know the effect of mineral and sugar solutions with different mineral concentrations 2%-5% with a carbohydrate percentage of 10% in an amount of 500 ml of water on some physical abilities and functional indicators. The study was conducted on football academy players aged 15-16 years, where the research sample amounted to 20 players and they were divided into two groups for each group (n = 10 experimental 1 took 2% mineral salts and 10% sugar) (n = 10 experimental 2 took 5% mineral salts and 10% sugar) ) They were trained three training units per week and the field experiment was conducted on them by holding matches within the academy’s football activity while they represented one of the teams. The study concluded that.